Development of Acacia spp. nanobactericides through nanoemulsions for controlling Xanthomonas oryzae pv. oryzae in rice - Shafiei, Siti Nur Sarah (2017)
Bacterial leaf blight caused by Xanthomonas oryzae pv. oryzae (Xoo), the main bacterial disease of paddy, causing serious yield loss during infection. Copper-based chemical fungicides and antibiotics have been applied to control this disease. Plant extracts have also shown potential to control Xoo since they may contain numerous active compounds. Acacia species are among the plants that have shown potential as antibacterial agents against numerous tested pathogens, especially the clinical isolates. In Peninsular Malaysia, Acacia auriculiformis and Acacia mangium are the two most common Acacia species. This study was conducted to determine the antibacterial activity of Acacia leaf extracts against Xoo, identify and quantify the phytochemical compounds content present in the extracts, suppress Xoo biofilm formation, and develop a nanoemulsion formulation using the Acacia leaf extract. Ethyl acetate and methanol leaf extracts from both species demonstrated inhibition of Xoo in vitro, while n-hexane and chloroform extracts failed to inhibit Xoo. The ethyl acetate and methanol leaf extracts demonstrated bactericidal and bacteriostatic effects based on their MIC index that was 2 (AAEA) and 8 (AMMH). However, methanol leaf extract showed better inhibition against Xoo. Scanning electron microscope (SEM) observation showed that the untreated Xoo cells were in healthy form, while the treated cells were deformed. The GC-MS analysis for AAEA and AMMH leaf extracts revealed that most of the active compounds belong to the phenolic acids, terpenoids, esters, fatty alcohols and other volatile compounds. The LC-MS/MS analysis gave equal numbers of identified compounds for both leaf extracts. The compounds belong to the flavonoids and phenolic compounds groups. Quantification of targeted active compounds demonstrated that rutin present abundantly in AAEA at 9.19 ng/mL and in AMMH at 48.80 ng/mL. The suppression of Xoo biofilm formation using AMMH leaf extract at various concentrations showed that the highest concentration of 12.5 mg/mL inhibited 81.25% of Xoo biofilm. Increased in the concentration of the extract had increased the loss of aggregation of the Xoo cells, as seen under confocal laser scanning microscopy (CLSM). The stable P2 AMMH nanoemulsion formulation possessed the mean size and zeta potential of 13.14 nm and -8.32 mV respectively. The nanoemulsion formulation was stable at both high (54±2°C) and low temperatures (0±2°C) at specified times. Glasshouse application demonstrated that P2 AMMH nanoemulsion formulation at a concentration of 6.25 mg/mL was able to control Xoo. The AUDPC value and protection index (PI) demonstrated by this concentration were almost similar to the treatment using streptomycin sulfate at concentrations of 0.2 mg/mL. This study confirmed that Acacia spp. leaf extract possess antibacterial activity against X. oryzae pv. oryzae.